Screening of Blood Plasma Cholesterol Level in Children from Families of Patients with Diabetes Mellitus - L.O. Prystupiuk (Zaslavsky O.Yu., 2015)
The objective of the work - to carry out a screening study of total cholesterol level in the blood plasma of children from families of patients with diabetes mellitus of both types. Materials and methods of the study. The content of fasting plasma cholesterol has been investigated in children aged 4-10 years. The cholesterol level was determined on automatic analyzers in the certified laboratories. Results of the study. 110 children (48 boys and 62 girls) were examined. In 40 % of boys, cholesterol indicators were within allowable values, in 42 % of patients - meet near-boundary values and in 18 % blood plasma cholesterol was above the norm. Similar figures for girls were equal to 68, 21 and 11 %. Conclusions. Considering that the cholesterol content, higher than normal one, in the blood plasma of children from families of patients with diabetes reaches 18 %, it is necessary to study cholesterolemia in these children from early childhood. For children with increased cholesterol levels in blood plasma, it is necessary to create conditions for its normalization - age-appropriate nutrition, physical activity and preventing the development of obesity in them.